2003
DOI: 10.1016/s0014-5793(03)00728-2
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein‐related protein‐2, a novel CC chemokine, can regulate preadipocyte migration and adipocyte differentiation

Abstract: Adipocytes not only store energy, but also secrete biologically active molecules called adipocytokines, which play a pivotal role in adipocyte-related pathological processes such as diabetes and cardiovascular disease. Recent studies have shown that preadipocyte/adipocyte expresses chemokines (e.g. monocyte chemoattractant protein-1, macrophage in£ammatory protein-1 alpha) which alter adipocyte function, indicating the involvement of chemokines in adipocyte-related pathologies. The current study investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
4
24
0
1
Order By: Relevance
“…Periosteum is composed of two layers populated by myofibroblasts and in literature it was demonstrated that in vitro myofibroblasts can develop into adipocytes when differentiation triggers change (23,24). Moreover, Kim verified two important facts: adipocytes have inflammatory chemokine receptors and they can migrate following the chemokine gradients (25). These results seem to confirm the hypothesis that PTL is caused by an inflammatory condition, which causes a change of the differentiation environment.…”
Section: Discussionsupporting
confidence: 64%
“…Periosteum is composed of two layers populated by myofibroblasts and in literature it was demonstrated that in vitro myofibroblasts can develop into adipocytes when differentiation triggers change (23,24). Moreover, Kim verified two important facts: adipocytes have inflammatory chemokine receptors and they can migrate following the chemokine gradients (25). These results seem to confirm the hypothesis that PTL is caused by an inflammatory condition, which causes a change of the differentiation environment.…”
Section: Discussionsupporting
confidence: 64%
“…To test this possibility, we compared by Northern blot analysis the expression of key adipocyte regulators, including Ppar␥, leptin, Srebp1, and Mrp2, in GON and SC fat pads of Mmp19 Ϫ/Ϫ and wild-type mice kept on a high-fat diet. Despite the fact that these genes have been shown to be involved in various steps of adipogenesis (17,23,33), we were unable to detect any significant differences in their expression levels in Mmp19 Ϫ/Ϫ mice (Fig. 4).…”
Section: Resultsmentioning
confidence: 69%
“…This data suggests that the increased extent of adipogenesis was not only a function of direct differentiation of human adipose progenitors, but that the exogenous cell sources also promoted increased migration and/or adipogenic differentiation of host preadipocytes within the scaffolds. Although the exact mechanisms of how the exogenous cells influenced host adipogenesis are unknown, previous studies have demonstrated the ability of adipocytes to secrete various paracrine factors which can positively influence both the migration and differentiation of preadipocytes [34,35]. Therefore, these mechanisms may also be involved in our system, however further experimentation is warranted.…”
Section: Discussionmentioning
confidence: 97%